PENGUATAN EFIKASI DIRI PADA PRIBADI INTROVERT - Lukman Hakim (LP2M IAI Al Khairat Pamekasan, 2021)
This article aims to explain the concept of strengthening self-efficacy in individuals who experience personal introverts through a community approach. The offer of the concept of activities designed by the supervisor by reaching out to intellectual, humanist and religiosity activities by emphasizing three main aspects of the individual namely cognitive, effective and psychomotor. Whereas in self-efficacy, increasing activities are needed: positive experiences (Mastery experience), other people's experiences (Vicarious experience), verbal persuasion and physiological and emotional states. Then the supervisor's offer to improve introverted individual selfefficacy is; Effective communication training activities and public speaking training, Creating live maps and presenting live maps, Community service activities or social services, Regular Community meetings, and My Forum sharing activities